The reactivity of Gallium-(I), -(II) and -(III) heterocycles towards group 15 substrates: Attempts to prepare gallium-terminal pnictinidene complexes. - BAKER, ROBERT (My University, 2006)
The reactivity of a series of Ga(I), Ga(II) and Ga(III) heterocyclic compounds towards a number of Group 15 substrates has been investigated with a view to prepare examples of gallium–terminal pnictinidene complexes. Although no examples of such complexes were isolated, a number of novel complexes have been prepared. The reactions of the gallium(I) N-heterocyclic carbene analogue, [K(tmeda)][:Ga{[N(Ar)C(H)]2}] (Ar = 2,6-diisopropylphenyl) with cyclo-(PPh)5 and PhN[double bond, length as m-dash]NPh led to the unusual anionic spirocyclic complexes, [{κ2P,P′-(PhP)4}Ga{[N(Ar)C(H)]2}]− and [{κ2N,C-PhNN(H)(C6H4)}Ga{[N(Ar)C(H)]2}]−, via formal reductions of the Group 15 substrate. The reaction of the digallane(4), [Ga{[N(Ar)C(H)]2}]2, with (Me3Si)N3 afforded the paramagnetic, dimeric imido–gallane complex, [{[N(Ar)C(H)˙]2}Ga{μ-N(SiMe3)}]2, via a Ga–Ga bond insertion process. In addition, the new gallium(III) phosphide, [GaI{P(H)Mes*}{[N(Ar)C(H)]2˙}], Mes* = C6H2But3-2,4,6; was prepared and treated with diazabicycloundecane (DBU) to give [Ga(DBU){P(H)Mes*}{[N(Ar)C(H)]2}], presumably via a gallium–terminal phosphinidene intermediate, [Ga{[double bond, length as m-dash]PMes*}{[N(Ar)C(H)]2˙}]. The possible mechanisms of all reactions are discussed, all new complexes have been crystallographically characterised and all paramagnetic complexes have been studied by ENDOR and/or EPR spectroscopy.
PUBLISHED